2020
DOI: 10.1186/s13075-020-02277-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of subclinical skin manifestation in patients with psoriasis and psoriatic arthritis by fluorescence optical imaging

Abstract: Objectives: To investigate the frequency of subclinical skin inflammation in both hands by fluorescence optical imaging (FOI) in patients with psoriasis/psoriatic arthritis (Pso/PsA) vs. rheumatoid arthritis (RA) and healthy individuals, and to correlate these findings with cardiovascular (CV) risk factors. Patients and methods: The FOI scans were analyzed retrospectively to detect clinically invisible skin enhancement (0-3 scale) in both hands without relationship to underlying joints or blood vessels. We fur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
2
11
0
1
Order By: Relevance
“…Active enthesitis and synovitis could be useful to identify subclinical PsA (178). Fluorescence optical imaging may be a helpful novel tool to analyze microcirculation in psoriasis/PsA patients (179).…”
Section: Psamentioning
confidence: 99%
“…Active enthesitis and synovitis could be useful to identify subclinical PsA (178). Fluorescence optical imaging may be a helpful novel tool to analyze microcirculation in psoriasis/PsA patients (179).…”
Section: Psamentioning
confidence: 99%
“…The early diagnosis and treatment of PsA are crucial to reduce the risk of joint damage, disability and comorbidities [ 7 , 8 , 9 ]. Since PsA usually occurs after the development of psoriasis [ 10 ], it is important that patients with psoriasis are routinely screened for signs of PsA.…”
Section: Introductionmentioning
confidence: 99%
“…After injection, a special camera detects the emissions of the fluorescent dye corresponding to the micro-vascularisation thus showing different patterns of inflammation. 32–35 Schmidt et al 33 applied this method to patients with psoriasis, PsA, RA and healthy controls and found that PsA and psoriasis patients have a specific FOI pattern that can be differentiated from healthy controls or even RA patients. Werner et al 32 performed a study where they demonstrated a correlation between the findings obtained by FOI, MRI, and US, while Wiemann et al 35 were able to differentiate between PsA and RA using this method.…”
Section: Resultsmentioning
confidence: 99%